(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The clinical research study of the interaction between the therapist and the client has as one of its main goals to identify any possible predictors of clinical outcomes. This research aims to identify and analyze vocal verbal episodes over the course of 21 sessions of behavior-analytic therapy. It was identified that the client had a behavioral pattern characterized as avoidance response, classified according some subcategories,and such pattern had a differentiated treatment.. The verbal behavior of the therapist was categorized through Multidimensional Therapeutic Skills Categorization System (SiMCCIT), from Zamignani (2007), and the signaled skills used were in avoidance blocking function. It was concluded that the avoidance blocking procedure intervention obtained clinically relevant changes in the client’s behavioral repertoire. For example increasing the following responses frequencies: self-observation, exposure of feelings, permittivity, access to private aversive events, self exposure to aversive stimuli, producing emotional tolerance.